2009
DOI: 10.1016/j.bioorg.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of catalysis and inhibition operative in the arginine deiminase from the human pathogen Giardia lamblia

Abstract: Giardia lamblia arginine deiminase (GlAD), the topic of this paper, belongs to the hydrolase branch of the guanidine-modifying enzyme superfamily, whose members employ Cys-mediated nucleophilic catalysis to promote deimination of L-arginine and its naturally occurring derivatives. G. lamblia is the causative agent in the human disease giardiasis. The results of RNAi/antisense RNA gene-silencing studies reported herein indicate that GlAD is essential for G. lamblia trophozoite survival and thus, a potential tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 44 publications
4
35
0
Order By: Relevance
“…OCT is known to be immunogenic in humans (31), but it did not induce any antibody response in immunized mice, nor did it confer protection (13). ADI could not be expressed successfully in the Salmonella vaccine strain and remains unexplored as a vaccine candidate (13), but it has been promoted as a drug candidate for therapeutic treatment of giardiasis due to the essentiality of ADI in trophozoites (25). Therefore, we aimed to answer the question of whether both Giardia proteins could be produced in and purified from the parasite, allowing subsequent interaction experiments with human epithelial cell lines in vitro, drug screenings, and vaccine trials in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCT is known to be immunogenic in humans (31), but it did not induce any antibody response in immunized mice, nor did it confer protection (13). ADI could not be expressed successfully in the Salmonella vaccine strain and remains unexplored as a vaccine candidate (13), but it has been promoted as a drug candidate for therapeutic treatment of giardiasis due to the essentiality of ADI in trophozoites (25). Therefore, we aimed to answer the question of whether both Giardia proteins could be produced in and purified from the parasite, allowing subsequent interaction experiments with human epithelial cell lines in vitro, drug screenings, and vaccine trials in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine, moreover, is the preferred substrate for energy production via the arginine dihydrolase (ADH) pathway that is usually found in prokaryotes (20). The secretion of two enzymes of this pathway, arginine deiminase (ADI) and ornithine carbamoyl transferase (OCT), by the parasite has recently been shown to be increased upon interaction with human cells (33), and they have also been suggested to be good drug targets (25). The possibility of producing potential virulence factors as recombinant proteins with native characteristics could further promote research on how Giardia subverts the intestinal milieu to its own benefit and will be valuable in drug screening.…”
mentioning
confidence: 99%
“…We cloned the adi gene present in strain WB-C6 and produced the respective recombinant enzyme, as well as an enzymatically inactive mutant form, ADI C424A (23), in which Cys at residue 424 was replaced with Ala, as hexahistidine-tagged proteins in E. coli. The recombinant proteins were purified, and the wild-type protein had an ADI activity level of 6.8 U/mg.…”
Section: Definition Of Experimental Conditions For Arginine Depletionmentioning
confidence: 99%
“…Nevertheless, the fold and function of this domain have not been elucidated. Previous reports have identified GiADI as a homodimer and have shown that the Cterminal domain is not involved in dimer interface formation (Knodler, Schofield, Gooley, & Edwards, 1997;Li et al, 2009). Based on this precedent, the 145 amino acids of the C-terminal domain were omitted during the modeling construction.…”
Section: <Figure 3 Here>mentioning
confidence: 96%
“…Since GiADI has been found in experimental studies as a homodimer enzyme (Li et al, 2009), the quaternary structure was constructed with the model selected above. For this purpose, the crystallographic structure of M. arginini ADI (Das et al, 2004) was used as a template to determine the three-dimensional arrangement of the homodimer.…”
Section: Giadi Homodimer Modelmentioning
confidence: 99%